Cryptotanshinone enhances wound healing in type 2 diabetes with modulatory effects on inflammation, angiogenesis and extracellular matrix remodelling - Min Song; Lu Chen; Lusha Zhang; Chunxiao Li; Joel Wake Coffie; Zhirui Fang; Liyuan Zhang; Shaoxia Wang; Xiumei Gao; Hong Wang (Taylor & Francis Group, 2020)
Context Cryptotanshinone (CT) is a diterpene quinone compound from Salvia miltiorrhiza Bge. Labiatae has been widely used in cardio-cerebral vascular diseases, which could be potentially effective in treating diabetic wounds. Objective This study evaluates the wound healing activity of CT by employing an excisional wound splinting model in db/db mice. Materials and methods Wounds were induced at the dorsum of non-diabetic (db/+) and diabetic (db/db) mice and treated with sodium carboxymethyl cellulose (CMC-Na) or 300 mg/kg/d CT for 16 days. Wound closure was measured every two days. Body weight, fasting blood glucose, re-epithelialization, granulation, leukocyte infiltration, capillary density, collagen deposition and expressions of CXCL1, CXCL2, VEGF, Ang-1, p-eNOS, eNOS, α-SMA, MMP2 and MMP9 were analysed. Expression of VEGF and tube formation was measured in vitro with human umbilical vein endothelial cells (HUVECs). Results CT significantly accelerated rate of wound closure, as the contraction ratio increased from 68% (non-treated group) to 83% (CT-treated group) at days 16 post-injury. A significant increase was observed in re-epithelialization and granulation tissue formation. Mechanistically, CT suppressed leukocyte infiltration and CXCL1 and CXCL2 expression. CT treatment also increased blood vessel density and expression level of VEGF, Ang-1 and p-eNOS. In vitro, CT boosted expression of VEGF and tube formation of endothelial cells. Moreover, extracellular matrix (ECM) remodelling was enhanced by CT via promoting fibroblast transformation and inhibiting MMP2 and MMP9. Conclusions Our study provides evidence that CT could be developed as a potential therapeutic agent for the treatment of chronic diabetic wound healing.